KEBAKARAN HUTAN DI INDONESIA DAN PROSES PENEGAKAN HUKUM SEBAGAI KOMITMEN DALAM MENGATASI DAMPAK PERUBAHAN IKLIM - Juliani Juliani (VERITAS, 2018)
Whereas from the side of legislation, there are enough laws and regulations that regulate fire and pollution or environmental damage. The problem is that law enforcement against forest fires has not been done seriously and optimally, this position reflects that forest fires are deliberate and become an important part of Indonesia's forestry and plantation problems. That the increase of forest / land burning level is at least also influenced by the development of timber industry that is not accompanied by the development of plantation forests as raw material, the amount of opportunity given by the Government to the entrepreneurs to convert the land into large-scale monoculture plantations such as oil palm and timber plantations (HTI), slow law enforcement responds to conversion and combustion measures by employers on the grounds of increasing PH levels (soil fertility).